Poultry farms as reservoirs of antibiotic-resistant Klebsiella pneumoniae: a “one health” concern - Karthika, Thekkevilayil P.; Anuranjini, Rajeev; Steni, Samson; Helan, Anna S.; Sivaprasad, Appukuttan N.; Jisha, Sarasamma; Deepthi, Govindakurup R.; Santhi, Sobitha W. (International Journal of Research in Medical Sciences, 2026)
Background: The emergence and spread of antibiotic-resistant bacteria have been largely attributed to the indiscriminate use of antibiotics in poultry farming, posing significant risks to human, animal, and environmental health. Increasing evidence links Klebsiella pneumoniae with multidrug resistance, highlighting its role as an emerging opportunistic pathogen. The present study aimed to isolate and evaluate antibiotic-resistant bacteria from chicken (Gallus gallus domesticus) droppings and assess their potential eco-health implications. Methods: Droppings were collected from a poultry farm located in Mavelikkara, Kerala, India. Microorganisms were isolated and characterized using standard microbiological protocols. Molecular identification of the isolates was carried out following established procedures. Confirmation of antibiotic-resistant strains was performed using species-specific polymerase chain reaction analysis. Results: Two antibiotic resistant strains of Klebsiella pneumoniae PB-01(PX376439) and PB-02(PX376441) strains were identified. Both strains exhibited resistance to commonly used antibiotics, including ampicillin, streptomycin, and erythromycin. Conclusions: Poultry farms may act as reservoirs of antibiotic resistance genes, facilitating their spread beyond ecological boundaries. This is supported by the isolation of multidrug-resistant Klebsiella pneumoniae from chicken fecal samples collected from the farm. The findings highlight the importance of integrated surveillance and prudent antibiotic stewardship to limit the spread of antibiotic resistance within the One Health framework.